Adhesive composition and adhesive sheet

By combining the acid-modified hydrogenated styrene-based block copolymer with a crosslinker, a polyphenylene ether resin and a tackifying resin, the insufficient weather resistance and heat resistance of styrene-based block copolymer at high temperatures is solved. The problem of this has achieved strong adhesion and weather resistance at high temperatures.

CN119137231AInactive Publication Date: 2024-12-13NITTO DENKO CORP
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202380037449.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2022-05-30
Filing Date
2023-05-18
Publication Date
2024-12-13
Estimated Expiration
Not applicable · inactive patent

AI Technical Summary

Technical Problem

The existing styrene-based block copolymers have insufficient weather resistance and heat resistance at high temperatures, resulting in a decrease in adhesive strength in hot melt applications, and the polymer cross-linking degree is too high after the cross-linking agent is added. Causes deterioration of adhesive properties.

Method used

By combining acid-modified hydrogenated styrene-based block copolymer with crosslinking agents that can react with acid, polyphenylene ether resins and tackifying resins (such as hydrogenated hydrocarbon resins and hydrogenated rosin esters), crosslinking and resins The addition of the adhesive improves the weather resistance and adhesion.

Benefits of technology

Maintaining strong adhesive strength at high temperatures and improving the weather and heat resistance of the adhesive, balanced adhesion and heat resistance by optimizing the ratio of crosslinking agent to resin.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119137231A_ABST
    Figure CN119137231A_ABST
Patent Text Reader

Abstract

The present invention provides an adhesive composition capable of forming an adhesive having a composition containing a styrene-based block copolymer capable of achieving a strong adhesive force, having a weatherability superior to that of an unhydrogenated composition, maintaining a strong adhesive force, and having a high heat resistance. Provided is an adhesive composition containing an acid-modified hydrogenated styrene-based block copolymer (A), a crosslinking agent (B) capable of reacting with an acid, a polyphenylene ether-based resin (C), and a tackifier resin (D). In some preferred embodiments, the ratio (WB / WC) of the content WB (wt%) of the crosslinking agent (B) capable of reacting with the acid to the content WC (wt%) of the polyphenylene ether resin (C) is 3 / 97 to 7 / 93.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to an adhesive composition comprising a styrene-based block copolymer. Furthermore, this invention relates to an adhesive sheet having an adhesive layer comprising a styrene-based block copolymer. This application claims priority to Japanese Patent Application No. 2022-87533, filed May 30, 2022, the entire contents of which are incorporated herein by reference. Background Technology

[0002] Typically, adhesives (also known as pressure-sensitive adhesives, hereinafter the same) exist as soft solids (viscoelastics) in a temperature range near room temperature, possessing the property of easily bonding to adherent materials under pressure. Utilizing these properties, adhesives are widely used as a bonding method with good workability and high bonding reliability in various industries, from household appliances to automobiles and office automation equipment. Representative compositions of such adhesives include polymers exhibiting rubber-like elasticity at room temperature and tackifying resins. For example, Patent Documents 1-3 describe adhesives comprising styrene-based block copolymers and tackifying resins.

[0003] Existing technical documents

[0004] Patent documents

[0005] Patent Document 1: Japanese Patent No. 5057626

[0006] Patent Document 2: Japanese Patent Application Publication No. 2000-212345

[0007] Patent Document 3: Japanese Patent No. 6820176 Summary of the Invention

[0008] The problem that the invention aims to solve

[0009] Styrene-isoprene-styrene block copolymers, such as styrene-isoprene-styrene (SIS) and styrene-butadiene-styrene (SBS), are widely used in tapes due to their excellent adhesion to difficult-to-bond materials such as polypropylene (PP) and polyethylene (PE). However, styrene-based block copolymers like SIS and SBS contain double bonds derived from conjugated dienes within their molecules, which can sometimes cause them to deteriorate due to ultraviolet radiation and heat. Therefore, among adhesives containing styrene-based block copolymers that achieve strong adhesion, adhesives with improved weather resistance would be useful.

[0010] Furthermore, styrene-based block copolymers exhibit cohesive strength due to the pseudo-crosslinking of styrene domains within the molecule. Therefore, at high temperatures above the glass transition temperature of polystyrene (typically around 90°C), the cohesive strength of styrene-based block copolymers tends to decrease. While this low cohesive strength at high temperatures is advantageous for use in hot-melt adhesives, it can also be a major cause of reduced heat resistance (e.g., adhesive strength at high temperatures) in the adhesive.

[0011] For adhesives using styrene-based block copolymers, methods have been investigated to improve heat resistance, including crosslinking the polymers in the adhesive using crosslinking agents, irradiation with active energy rays, and adding resins with high softening points. For example, in cited reference 1, a composition containing a functionalized block copolymer crosslinked with a crosslinking agent was used to improve solvent resistance and cohesive strength at high temperatures. However, if the amount of crosslinking agent added is increased to improve heat resistance, the degree of crosslinking of the polymer becomes too high, and there is a tendency for other adhesive properties (such as adhesive strength) to decrease.

[0012] Furthermore, in Patent Document 2, efforts were made to improve heat resistance by using aromatic vinyl compounds-conjugated diene block copolymers in conjunction with vinyl polymers. However, polyolefins such as vinyl polymers lack adhesive properties, and therefore the adhesive properties of the adhesive tend to decrease due to the addition of this polyolefin. In addition, in cited document 3, efforts were made to improve high-temperature adhesion by using styrene elastomers in conjunction with polyether resins, but if the content of the polyether resin is too high, it is difficult to obtain sufficient adhesive strength, thus limiting the improvement in heat resistance. Therefore, the compositions proposed in Patent Documents 1-3 have limitations in balancing sufficient adhesive strength and high heat resistance.

[0013] The present invention was made in view of the above-described situation, and its object is to provide an adhesive composition that forms an adhesive comprising a styrene-based block copolymer capable of achieving strong adhesion, exhibiting superior weather resistance compared to the unhydrogenated composition, maintaining strong adhesion, and possessing high heat resistance. Another object relates to providing an adhesive sheet comprising an adhesive comprising a styrene-based block copolymer capable of achieving strong adhesion, exhibiting superior weather resistance compared to the unhydrogenated composition, maintaining strong adhesion, and possessing high heat resistance.

[0014] Solution for solving the problem

[0015] According to this specification, an adhesive composition is provided comprising an acid-modified hydrogenated styrene block copolymer (A), an acid-reactive crosslinking agent (B), a polyphenylene ether resin (C), and a tackifying resin (D). In the adhesive composition described above, the use of the hydrogenated styrene block copolymer (A) tends to improve weather resistance compared to the use of an unhydrogenated styrene block copolymer. Furthermore, the acid-modified hydrogenated styrene block copolymer (A) is crosslinked by reacting with the acid-reactive crosslinking agent (B). Additionally, the polyphenylene ether resin (C) is added to the adhesive composition. These additions improve heat resistance. Furthermore, the addition of the tackifying resin (D) improves adhesive properties such as adhesion strength. The adhesive composition according to the above configuration forms an adhesive whose composition includes a styrene block copolymer capable of achieving strong adhesion, exhibits superior weather resistance compared to the unhydrogenated composition, maintains sufficient adhesion strength, and possesses high heat resistance.

[0016] In some preferred adhesive compositions, the ratio (WB / WC) of the content of the crosslinking agent (B) WB [weight %] to the content of the polyphenylene ether resin (C) WC [weight %] is 3 / 97 or more and 7 / 93 or less. By setting the ratio of the polyphenylene ether resin (C) to the crosslinking agent (B) within the above range, it is easy to achieve both high heat resistance and excellent adhesion.

[0017] In some preferred embodiments, the acid-modified hydrogenated styrene block copolymer (A) is a maleic anhydride-modified hydrogenated styrene block copolymer (e.g., a maleic anhydride-modified styrene-ethylene-butene-styrene block copolymer). In adhesive compositions comprising the maleic anhydride-modified hydrogenated styrene block copolymer as described above as the styrene block copolymer (A), the effects of the techniques disclosed herein can preferably be achieved.

[0018] In some preferred embodiments, the acid-reactive crosslinking agent (B) is a metal compound. The effects of the technology disclosed herein are preferably realized in adhesives containing a metal compound as an acid-reactive crosslinking agent. Preferred examples of the metal compound include metal acetylacetone (e.g., trialuminum acetylacetone). In some preferred embodiments, the content of the acid-reactive crosslinking agent (B) is 0.3 parts by weight or more and 1.3 parts by weight or less relative to 100 parts by weight of the acid-modified hydrogenated styrene block copolymer (A).

[0019] In some preferred embodiments, the polyphenylene ether resin (C) is polyphenylene ether. The effects of the techniques disclosed herein can preferably be achieved in adhesive compositions containing polyphenylene ether. In some preferred embodiments, the content of the polyphenylene ether resin (C) is 10 parts by weight or more and 20 parts by weight or less relative to 100 parts by weight of the acid-modified hydrogenated styrene block copolymer (A).

[0020] In some preferred embodiments, the tackifying resin (D) comprises a hydrogenated hydrocarbon resin and a hydrogenated rosin ester. Both the hydrogenated hydrocarbon resin and the hydrogenated rosin ester are hydrogenated; therefore, based on the composition of the tackifying resin (D) comprising both hydrogenated hydrocarbon resin and hydrogenated rosin ester, improved adhesion and weather resistance can be achieved. The effects of the technology disclosed herein are preferably realized in adhesives comprising hydrogenated hydrocarbon resin and hydrogenated rosin ester. In some preferred embodiments, the content of the hydrogenated hydrocarbon resin is 100 parts by weight or more and 150 parts by weight or less relative to 100 parts by weight of the acid-modified hydrogenated styrene block copolymer (A). Furthermore, in some preferred embodiments, the content of the hydrogenated rosin ester is 30 parts by weight or more and 50 parts by weight or less relative to 100 parts by weight of the acid-modified hydrogenated styrene block copolymer (A).

[0021] In some preferred embodiments, the adhesive composition further comprises a softener (E). Adding a softener can further improve the adhesive strength. Various softeners can be used as the softener (E) without particular limitation; for example, liquid hydrocarbons can be used. In some preferred embodiments, the content of the softener is 25 parts by weight or more and 50 parts by weight less relative to 100 parts by weight of the acid-modified hydrogenated styrene block copolymer (A). Setting the content of the softener within the above range makes it easier to improve the adhesive strength.

[0022] Furthermore, according to this specification, an adhesive sheet having an adhesive layer formed from any of the adhesive compositions disclosed herein is provided. The adhesive sheet described above can exhibit high adhesion and possess excellent weather resistance and high heat resistance.

[0023] It should be noted that an invention that appropriately combines the elements described in this specification may also be included within the scope of protection of an invention for which patent protection is sought under this patent application. Attached Figure Description

[0024] Figure 1 This is a schematic cross-sectional view showing the configuration of an adhesive sheet (double-sided adhesive sheet with a substrate) according to one embodiment.

[0025] Figure 2 This is a schematic cross-sectional view showing the structure of an adhesive sheet (a substrate-free double-sided adhesive sheet) according to another embodiment.

[0026] Figure 3 This is a schematic cross-sectional view showing the configuration of an adhesive sheet (a single-sided adhesive sheet with a substrate) according to another embodiment. Detailed Implementation

[0027] The preferred embodiments of the present invention will now be described. For those skilled in the art, matters other than those specifically mentioned in this specification, and matters necessary for implementing the present invention, can be understood based on the implications of implementing the invention described herein and common technical knowledge at the time of application. The present invention can be implemented based on the disclosures in this specification and common technical knowledge in the field.

[0028] It should be noted that in the following figures, components / parts that perform the same function are sometimes labeled with the same reference numerals, and sometimes repeated descriptions are omitted or simplified. Furthermore, the embodiments described in the figures are schematic for the purpose of clearly illustrating the invention and do not accurately represent the dimensions or scale of the actual product provided.

[0029] As described above, "adhesive" in this specification refers to a material that is a soft solid (viscoelastic) in a temperature range near room temperature and has the property of easily adhering to substrates under pressure. The adhesives disclosed herein can also be understood as solid components of an adhesive composition or constituent components of an adhesive layer.

[0030] In this specification, "styrene-based block copolymer" refers to a polymer having at least one styrene block. The aforementioned styrene block refers to a segment with styrene as the main monomer. A segment consisting solely of styrene is a typical example of a styrene block as described here. In this specification, "hydrogenated styrene-based block copolymer" refers to a styrene-based block copolymer containing at least a portion of a hydride formed by hydrogenation (addition of hydrogen atoms). Furthermore, "styrene-ethylene-butene-styrene block copolymer" refers to a polymer formed by hydrogenating at least a portion of the double bonds of a styrene-butadiene block copolymer. Here, "styrene-butadiene block copolymer" refers to a polymer having at least one styrene block and at least one butadiene block (a segment with butadiene as the main monomer).

[0031] In this specification, the "styrene content" of styrene-based block copolymers (including hydrogenated styrene-based block copolymers and acid-modified hydrogenated styrene-based block copolymers) refers to the proportion of styrene by weight in the total weight of the block copolymer. The styrene content can be determined using NMR (nuclear magnetic resonance spectroscopy).

[0032] Furthermore, the proportion of diblock copolymers in styrene-based block copolymers (hereinafter sometimes referred to as the "diblock ratio" or "diblock proportion") can be determined by the following method: The styrene-based block copolymer is dissolved in tetrahydrofuran (THF). Four high-performance liquid chromatography (HPLC) columns (two stages each, totaling four stages) manufactured by Tosoh Corporation (GS5000H and G4000H) are connected in series, with THF as the mobile phase. The HPLC is performed at 40°C and a flow rate of 1 mL / min. The peak area corresponding to the diblock copolymer is determined from the resulting chromatogram. Then, the percentage of the peak area corresponding to the diblock copolymer relative to the total peak area is calculated, thereby determining the diblock ratio.

[0033] In this specification, "weight" can be interpreted as "mass". For example, "weight%" can be interpreted as "mass%", and "parts by weight" can be interpreted as "parts by mass".

[0034] <Adhesive Composition>

[0035] (Styrene-based block copolymer)

[0036] The adhesive compositions disclosed herein comprise styrene-based block copolymers. These styrene-based block copolymers are block copolymers of a monovinyl-substituted aromatic compound and a conjugated diene compound. The monovinyl-substituted aromatic compound refers to a compound having a vinyl functional group bonded to an aromatic ring. Representative examples of the aromatic ring include benzene rings (which may be benzene rings substituted with non-vinyl functional groups (e.g., alkyl groups)). Specific examples of the monovinyl-substituted aromatic compounds include styrene, α-methylstyrene, vinyltoluene, vinylxylene, etc. Specific examples of the conjugated diene compounds include 1,3-butadiene, isoprene, etc. Such block copolymers can be used alone or in combination with two or more.

[0037] It should be noted that styrene-based block copolymers are components that can be used as the matrix polymer of an adhesive. The "matrix polymer" of an adhesive refers to the main component (i.e., the component that accounts for more than 50% by weight of the rubber-like polymer) contained in the adhesive (a polymer that exhibits rubber elasticity in a temperature range near room temperature).

[0038] In the above-mentioned styrene-based block copolymer, the copolymerization ratio of the monovinyl-substituted aromatic compound (two or more of which may be used in combination) in the A segment (hard segment) is preferably 70% by weight or more (more preferably 90% by weight or more, and substantially 100% by weight). In the above-mentioned styrene-based block copolymer, the copolymerization ratio of the conjugated diene compound (two or more of which may be used in combination) is preferably 70% by weight or more (more preferably 90% by weight or more, and substantially 100% by weight). According to the above-mentioned block copolymer, adhesive sheets with higher performance can be achieved.

[0039] The aforementioned styrene-based block copolymers can be diblock, triblock, radial, or mixtures thereof. In triblock and radial copolymers, it is preferable to place A-segments (e.g., styrene blocks) at the ends of the polymer chains. This is because A-segments located at the ends of the polymer chains tend to aggregate and form domains, thereby creating a pseudo-crosslinked structure and increasing the cohesiveness of the adhesive.

[0040] As for the styrene-based block copolymers disclosed herein, from the viewpoint of adhesive strength (peel strength) of the adhered objects, block copolymers with a diblock ratio of 30% by weight or more (more preferably 40% by weight or more, further preferably 50% by weight or more, particularly preferably 60% by weight or more, and typically 65% ​​by weight or more) are preferred. From the viewpoint of peel strength, block copolymers with a diblock ratio of 70% by weight or more are particularly preferred. Furthermore, from the viewpoint of cohesiveness, block copolymers with a diblock ratio of 90% by weight or less (more preferably 85% by weight or less, for example, 80% by weight or less) are preferred. For example, block copolymers with a diblock ratio of 60 to 85% by weight are preferred, and block copolymers with a diblock ratio of 70 to 85% by weight (for example, 70 to 80% by weight) are more preferred.

[0041] The adhesive composition disclosed herein includes, as the aforementioned styrene-based block copolymer, a hydrogenated styrene-based block copolymer comprising at least a portion of the styrene-based block copolymer. The hydrogenated styrene-based block copolymer has at least a portion of the double bonds within the styrene-based block copolymer molecule with added hydrogen atoms; therefore, adhesives containing the aforementioned hydrogenated styrene-based block copolymer tend to exhibit improved weather resistance (typically, the property of suppressing degradation caused by ultraviolet light and heat). In the disclosed technology, the proportion of hydrogenated styrene-based block copolymer in the styrene-based block copolymer contained in the adhesive is preferably 70% by weight or more, more preferably 80% by weight or more, and even more preferably 90% by weight or more. In some preferred embodiments, the aforementioned styrene-based block copolymer is substantially entirely (e.g., 95-100% by weight) hydrogenated styrene-based block copolymer. With such a composition, the weather resistance of the adhesive is easily improved.

[0042] Examples of hydrogenated styrene-based block copolymers include styrene-ethylene-butene-styrene (SEBS) block copolymers, styrene-ethylene-propylene-styrene (SEPS) block copolymers, and styrene-ethylene-ethylene-propylene-styrene (SEEPS). Additionally, examples of hydrogenated styrene-based block copolymers include styrene-isobutylene-styrene (SIBS) block copolymers. From the viewpoint of easily adjusting the adhesive strength to a preferred range, SEBS block copolymers, SEPS copolymers, and SIBS block copolymers are preferred, with SEBS block copolymers being more preferred. These hydrogenated styrene-based block copolymers can be used alone or in combination of two or more.

[0043] The proportion of SEBS block copolymer in the styrene-based block copolymer contained in the adhesive is not particularly limited, but from the viewpoint of easily adjusting the adhesive strength to a preferred range, it is preferably 70% by weight or more, more preferably 80% by weight or more, and even more preferably 90% by weight or more. The aforementioned styrene-based block copolymer may be substantially entirely (e.g., 95 to 100% by weight) SEBS block copolymer.

[0044] The aforementioned hydrogenated styrene-based block copolymers can be diblock, triblock, radial, or mixtures thereof. In triblock and radial copolymers, styrene blocks are preferably disposed at the ends of the polymer chains. This is because styrene blocks disposed at the ends of the polymer chains tend to aggregate and form styrene domains, thereby creating a pseudo-crosslinked structure and increasing the cohesiveness of the adhesive. From the viewpoint of adhesive strength (peel strength) of the adhered objects, block copolymers with a diblock ratio of 30% by weight or more (more preferably 40% by weight or more, further preferably 50% by weight or more, particularly preferably 60% by weight or more, and typically 65% ​​by weight or more) are preferred as used in the technology disclosed herein. Hydrogenated styrene-based block copolymers with a diblock ratio of 70% by weight or more (e.g., 75% by weight or more) are also possible. Furthermore, from the viewpoint of cohesiveness, hydrogenated styrene block copolymers with a diblock ratio of 90% by weight or less (more preferably 85% by weight or less, for example, 80% by weight or less) are preferred. From the viewpoint of achieving a good balance between adhesive strength and heat resistance using the techniques disclosed herein, hydrogenated styrene block copolymers with a diblock ratio of 60 to 85% by weight are preferred, and hydrogenated styrene block copolymers with a diblock ratio of 70 to 85% by weight (for example, 70 to 80% by weight) are more preferred.

[0045] The styrene content of the aforementioned hydrogenated styrene block copolymer can be, for example, 5 to 40% by weight. From the viewpoint of cohesiveness, hydrogenated styrene block copolymers with a styrene content of 10% by weight or more (more preferably more than 10% by weight, for example, 12% by weight or more) are generally preferred. Furthermore, from the viewpoint of peel strength, the styrene content of the hydrogenated styrene block copolymer is preferably 35% by weight or less (typically 30% by weight or less, more preferably 25% by weight or less), and particularly preferably 22% by weight or less (typically less than 20% by weight, for example, 18% by weight or less). From the viewpoint of obtaining high adhesive strength, hydrogenated styrene block copolymers with a styrene content of 10 to 22% by weight are preferred.

[0046] The adhesive composition disclosed herein comprises, as a styrene-based block copolymer, an acid-modified hydrogenated styrene-based block copolymer (A). The acid-modified hydrogenated styrene-based block copolymer (A) typically refers to a polymer in which functional groups such as carboxyl groups and anhydride groups are introduced. The acid-modified sites (typically carboxyl groups and anhydride groups) in the acid-modified hydrogenated styrene-based block copolymer (A) may become reaction sites with the crosslinking agent (B) described later. Therefore, if a crosslinking agent is used together with the acid-modified hydrogenated styrene-based block copolymer (A), the degree of crosslinking of the hydrogenated styrene-based block copolymer increases, and its heat resistance is easily improved.

[0047] The preferred ranges for the diblock ratio and styrene content of the acid-modified hydrogenated styrene block copolymer (A) used herein are the same as the preferred diblock ratio and preferred styrene content in the hydrogenated styrene block copolymers described above.

[0048] There are no particular limitations on the method for acid modification of hydrogenated styrene-based block copolymers. Examples include: polymerizing a monomer with an anhydride group as one of the raw materials for manufacturing the hydrogenated styrene-based block copolymer with other raw materials; introducing an anhydride group into the side chain after synthesizing the hydrogenated styrene-based block copolymer; and performing a grafting reaction. More specifically, examples include: copolymerizing an anhydride of an appropriate amount of olefinically unsaturated carboxylic acids such as maleic anhydride; and performing a grafting reaction using an anhydride of an appropriate amount of olefinically unsaturated carboxylic acids such as maleic anhydride and a peroxide after synthesizing the hydrogenated styrene-based block copolymer. Furthermore, an appropriate amount of olefinically unsaturated carboxylic acids such as maleic acid can be used instead of anhydrides.

[0049] In some embodiments, the acid used to modify the aforementioned hydrogenated styrene-based block copolymer can be at least one selected from unsaturated monocarboxylic or polycarboxylic acids containing about 3 to 10 carbon atoms and acid anhydrides. Examples of such acids include fumaric acid, itaconic acid, citraconic acid, acrylic acid, maleic anhydride, itaconic anhydride, and citraconic anhydride.

[0050] From the perspective of being able to preferably adjust the degree of crosslinking, maleic anhydride is preferably used as the acid. That is, as the acid-modified hydrogenated styrene block copolymer (A) disclosed herein, it is preferable to use a maleic anhydride-modified hydrogenated styrene block copolymer that has been acid-modified using maleic anhydride. In some preferred embodiments, a maleic anhydride-modified SEBS block copolymer can be used as the acid-modified hydrogenated styrene block copolymer (A). If such a block copolymer is used, it can be used together with the crosslinking agent described later, thereby achieving an adhesive that maintains strong adhesion and has excellent weather resistance and high heat resistance.

[0051] Specific examples of acid-modified hydrogenated styrene block copolymers (A) include “TUFTECM1913” (manufactured by Asahi Kasei Chemicals), “FG1924” (manufactured by Kraton), and “FG1901” (manufactured by Kraton).

[0052] (Cross-linking agent (B) that can react with acid)

[0053] The adhesive composition disclosed herein is characterized by containing an acid-reactive crosslinking agent (B) (hereinafter also simply referred to as "crosslinking agent (B)"). By using the acid-reactive crosslinking agent (B) together with an acid-modified hydrogenated styrene block copolymer (A), the styrene block copolymer tends to crosslink, resulting in improved heat resistance.

[0054] Here, the "acid" in the crosslinking agent (B) that can react with acid is typically a compound containing carboxyl or anhydride groups as functional groups.

[0055] As a crosslinking agent (B), any crosslinking agent that can react with acid can be used without particular limitation. Examples of crosslinking agents (B) that can react with acid include isocyanate-based crosslinking agents, epoxy-based crosslinking agents, and metal compounds. Crosslinking agent (B) can be used alone or in combination of two or more.

[0056] Furthermore, as the crosslinking agent (B), a solid or powder crosslinking agent is preferred. In particular, when applying the adhesive composition disclosed herein to a hot-melt adhesive used in material bonding at high temperatures, a solid or powder crosslinking agent reduces concerns about flammability and harm to human health caused by volatile components compared to organic solvent dilution systems or liquid crosslinking agents. From the above perspective, a metal compound can be preferably used as the crosslinking agent (B).

[0057] Examples of metal compounds include metal alkoxide crosslinking agents, metal complex crosslinking agents, and metal salt crosslinking agents. Among these, metal complex crosslinking agents are preferred from the perspective of crosslinking reaction rate. Metal complex crosslinking agents are compounds with multifunctionality, where multivalent metal atoms are bonded (covalently, coordinately, etc.) to organic compounds (complexing agents). Examples of multivalent metal atoms in metal complex crosslinking agents include: Group IIA elements of the periodic table such as magnesium (Mg), calcium (Ca), strontium (Sr), and barium (Ba); Group IIIB elements of the periodic table such as scandium (Sc), yttrium (Y), lanthanides [lanthanum (La), cerium (Ce), etc.], and actinides [actinium (Ac), etc.]; Group IVB elements of the periodic table such as titanium (Ti) and zirconium (Zr); Group V elements of the periodic table such as vanadium (V), niobium (Nb), and tantalum (Ta); and other elements of the periodic table such as chromium (Cr), molybdenum (Mo), and tungsten (W). Elements in the periodic table include: Group VIB elements; Group VIIB elements such as manganese (Mn); Group VIII elements such as iron (Fe); Group VIII elements such as cobalt (Co); Group VIII elements such as nickel (Ni), palladium (Pd), and platinum (Pt); Group IB elements such as copper (Cu), silver (Ag), and gold (Au); Group IIB elements such as zinc (Zn); Group IIIA elements such as aluminum (Al), gallium (Ga), and indium (In); and Group IVA elements such as tin (Sn) and lead (Pb). In metal complex crosslinking agents, multivalent metal atoms can be used alone or in combination of two or more. Preferably, aluminum, zirconium, and titanium are used as multivalent metal atoms, with aluminum being particularly preferred.

[0058] Therefore, as metal complex crosslinking agents, for example, aluminum complex crosslinking agents, zirconium complex crosslinking agents, titanium complex crosslinking agents, chromium complex crosslinking agents, cobalt complex crosslinking agents, copper complex crosslinking agents, iron complex crosslinking agents, nickel complex crosslinking agents, vanadium complex crosslinking agents, zinc complex crosslinking agents, indium complex crosslinking agents, calcium complex crosslinking agents, magnesium complex crosslinking agents, manganese complex crosslinking agents, yttrium complex crosslinking agents, cerium complex crosslinking agents, strontium complex crosslinking agents, barium complex crosslinking agents, molybdenum complex crosslinking agents, lanthanum complex crosslinking agents, tin complex crosslinking agents, etc., are preferred, with aluminum complex crosslinking agents, zirconium complex crosslinking agents, and titanium complex crosslinking agents (more preferably aluminum complex crosslinking agents).

[0059] On the other hand, in metal complex crosslinking agents, there are no particular limitations on the atoms in the complexing agent that bond with polyvalent metal atoms, but oxygen atoms are preferred. Therefore, examples of complexing agents include ester compounds, alcohol compounds, carboxylic acid compounds, ether compounds, and ketone compounds. More specifically, examples of complexing agents include: β-dicarbonyl compounds [e.g., acetylacetone, 2,4-hexanedione, 2,4-heptanedione, 3,5-heptanedione, 2,4-octanedione, 3,5-octanedione, 2,4-nonanedione, 3,5-nonanedione, 5-methyl-2,4-hexanedione, etc. β-diketones; methyl acetoacetate, ethyl acetoacetate, propyl acetoacetate, isopropyl acetoacetate, butyl acetoacetate, isobutyl acetoacetate, sec-butyl acetoacetate, tert-butyl acetoacetate, 2-ethylhexyl acetoacetate, dodecyl acetoacetate, etc. β-keto esters (acetoacetate C 1-20 Alkyl esters, etc.; β-diesters such as diethyl malonate, etc.; carbonyl compounds with hydroxyl or amino groups at the β-position (e.g., diacetone alcohol, diacetone amine, salicylaldehyde, methyl salicylate, N-methylsalicylic acid amide, etc.). Complexing agents can be used alone or in combination of two or more.

[0060] In some preferred embodiments, acetylacetone metal (e.g., tri(acetylacetone)aluminum) can be used as the crosslinking agent for the metal complex system.

[0061] In the case of metal complex crosslinking agents, such as aluminum complex crosslinking agents with aluminum as the polyvalent metal atom, examples of aluminum complex crosslinking agents include: tri(acetylacetone)aluminum, tri(propionylacetone)aluminum, etc.; tri(acetoethyl acetoacetate)aluminum, tri(tert-butyl acetoacetate)aluminum, etc.; mono(acetylacetone)bis(acetoethyl acetoacetate)aluminum, mono(acetylacetone)bis(isobutyl acetoacetate)aluminum, mono(acetylacetone)bis(2-ethylhexyl acetoacetate)aluminum. Aluminum complexes include mono(acetylacetone) and bis(dodecyl acetoacetate) aluminum [(mono or bis)(acetylacetone)][(bis or mono)(alkyl acetoacetate)] aluminum; aluminum diisopropanol derivatives, bis(acetylacetone) aluminum monoisopropanol derivatives, etc. [(mono or bis)(acylacetone)] aluminum [(di or mono) alcohol]; aluminum diisopropanol derivatives, bis(ethyl acetoacetate) aluminum monoisopropanol derivatives, etc. [(mono or bis)(alkyl acetoacetate)] aluminum [(di or mono) alcohol], etc. It should be noted that tri(acetylacetone) aluminum and tri(ethyl acetoacetate) aluminum are preferred as crosslinking agents for aluminum complex systems.

[0062] In addition, as metal complex crosslinking agents other than aluminum complex crosslinking agents (zirconium complex crosslinking agents, titanium complex crosslinking agents, etc.), crosslinking agents corresponding to the aluminum complex crosslinking agents exemplified above can be listed.

[0063] It should be noted that, as the crosslinking agent (B), when using crosslinking agents other than metal complex crosslinking agents, isocyanate-based crosslinking agents and epoxy-based crosslinking agents are preferred. Furthermore, metal complex crosslinking agents can be used in combination with other crosslinking agents (isocyanate-based crosslinking agents, epoxy-based crosslinking agents, etc.).

[0064] As isocyanate-based crosslinking agents, multifunctional isocyanate compounds with two or more functions can be used. Examples include aromatic isocyanates such as toluene diisocyanate, xylene diisocyanate, polymethylene polyphenyl diisocyanate, tris(p-isocyanate phenyl)thiophosphate, and diphenylmethane diisocyanate; alicyclic isocyanates such as isophorone diisocyanate; and aliphatic isocyanates such as hexamethylene diisocyanate. Commercially available examples include trimethylolpropane / toluene diisocyanate trimer adducts (manufactured by Tosoh Corporation, trade name "Coronate L"), trimethylolpropane / hexamethylene diisocyanate trimer adducts (manufactured by Tosoh Corporation, trade name "Coronate HL"), and isocyanurate derivatives of hexamethylene diisocyanate (manufactured by Tosoh Corporation, trade name "Coronate HX"). These can be used alone or in combination of two or more.

[0065] As an epoxy-based crosslinking agent, crosslinking agents having two or more epoxy groups in one molecule can be used without particular limitation. Preferably, epoxy-based crosslinking agents have 3 to 5 epoxy groups in one molecule. Specific examples of epoxy-based crosslinking agents include N,N,N',N'-tetraglycidyl-m-phenylenediamine, 1,3-bis(N,N-diglycidylaminomethyl)cyclohexane, 1,6-hexanediol diglycidyl ether, polyethylene glycol diglycidyl ether, and polyglycerol polyglycidyl ether. Commercially available epoxy crosslinking agents include those manufactured by Mitsubishi Gas Chemical under the trade names "TETRAD-X" and "TETRAD-C", those manufactured by DIC under the trade name "EPICLON CR-5L", those manufactured by Nagase ChemteX under the trade names "Denacol EX-512", "Denacol EX-411", and "Denacol EX-321", and those manufactured by Nissan Chemical Industries under the trade name "TEPIC-G". These can be used individually or in combination of two or more.

[0066] The content of the crosslinking agent (B) is not particularly limited. From the viewpoint of improving the degree of crosslinking and thus improving heat resistance, the content of the crosslinking agent (B) relative to 100 parts by weight of the acid-modified hydrogenated styrene block copolymer (A) is preferably about 0.01 parts by weight or more, more preferably 0.1 parts by weight or more, further preferably 0.2 parts by weight or more, and particularly preferably 0.3 parts by weight or more. Furthermore, the content of the crosslinking agent (B) relative to 100 parts by weight of the acid-modified hydrogenated styrene block copolymer (A) is generally suitably set to 10 parts by weight or less, preferably 5 parts by weight or less, more preferably 3 parts by weight or less, further preferably 2 parts by weight or less (e.g., 1.5 parts by weight or less), and particularly preferably 1.3 parts by weight or less. According to the technology disclosed herein, even when the content of the crosslinking agent (B) is limited as described above, improved heat resistance can be achieved.

[0067] (Polyphenylene ether resin (C))

[0068] The adhesive composition disclosed herein comprises a polyphenylene ether resin (C). Examples of polyphenylene ether resins include polyphenylene ether resins having an aromatic polyether structure and modified polyphenylene ether resins alloyed with the polyphenylene ether resin as the main component and other synthetic resins. In this specification, "main component" means a component that comprises more than 50% by weight of the total component.

[0069] By using a styrene-based block copolymer in conjunction with a polyphenylene ether resin (C), an adhesive with improved heat resistance and good adhesion at high temperatures can be achieved. While not specifically limited in interpretation, the styrene domains of the polyphenylene ether resin (C) are compatible with those of the styrene-based block copolymer, thereby improving the adhesive's adhesion properties at high temperatures (e.g., above 90°C). As the polyphenylene ether resin (C), a polyphenylene ether resin with high compatibility with styrene-based block copolymers is preferred. From the above perspective, a polyphenylene ether resin is preferred as the polyphenylene ether resin (C). Here, "polyphenylene ether resin" refers to a polymer compound containing phenoxy and thiophenoxy groups as repeating units.

[0070] In the technology disclosed herein, the softening point of the polyphenylene ether resin (C) (e.g., polyphenylene ether resin) is not particularly limited, but is preferably higher than the glass transition temperature of polystyrene (typically about 90°C). In some preferred embodiments, the softening point of the polyphenylene ether resin is 90°C or higher, more preferably 120°C or higher, and even more preferably 150°C or higher (e.g., 160°C or higher). The upper limit of the softening point of the polyphenylene ether resin is not particularly limited. The softening point of the polyphenylene ether resin (C) can be below 200°C, below 180°C, or below 170°C.

[0071] The content of polyphenylene ether resin (C) (e.g., polyphenylene ether resin) in the adhesive composition is not particularly limited, and an appropriate amount can be used in a manner that achieves the desired effect. In some preferred embodiments, from the viewpoint of improving heat resistance (e.g., improving adhesive strength at high temperatures), the content of polyphenylene ether resin is 1 part by weight or more, more preferably 5 parts by weight or more, and even more preferably 10 parts by weight or more, relative to 100 parts by weight of the styrene block copolymer. From the viewpoint of keeping the viscoelasticity of the adhesive within a suitable range, the content of polyphenylene ether resin (C) is generally suitably set to 75 parts by weight or less, preferably 50 parts by weight or less, more preferably 25 parts by weight or less, and even more preferably 20 parts by weight or less, relative to 100 parts by weight of the styrene block copolymer.

[0072] From the viewpoint of improving adhesion, the content of polyphenylene ether resin (C) is preferably adjusted to have a specific relationship with the content of crosslinking agent (B). In some preferred embodiments, the ratio (WB / WC) of the crosslinking agent (B) content WB [weight %] to the polyphenylene ether resin (C) content WC [weight %] is 1 / 99 to 10 / 90, more preferably 2 / 98 to 12 / 88, and even more preferably 3 / 97 to 7 / 93. By setting the content ratio of crosslinking agent (B) to polyphenylene ether resin (C) within the above range, a good balance can be achieved between improved heat resistance and strong adhesion.

[0073] (Tackifying Resin (D))

[0074] The adhesive composition disclosed herein comprises a tackifying resin (D). The tackifying resin can be used alone or in combination of two or more. There are no particular limitations on the tackifying resin; for example, petroleum-based tackifying resins and natural-based tackifying resins can be used. Here, the petroleum-based tackifying resin is a compound derived from petroleum resources, having a chemical structure derived from petroleum resources, and its adhesive properties are imparted to the adhesive based on its compatibility with the adhesive and its chemical properties. Furthermore, the natural-based tackifying resin is a compound containing components derived from natural substances, having a chemical structure derived from natural substances, and its adhesive properties are imparted to the adhesive based on its compatibility with the adhesive and its chemical properties. In the technology disclosed herein, based on the chemical structures of petroleum-based and natural-based tackifying resins, one or more of them are appropriately selected to design an adhesive with a good balance between adhesive strength and heat resistance.

[0075] Examples of petroleum-based tackifying resins include aliphatic (C5 series) petroleum resins, aromatic (C9 series) petroleum resins, aliphatic / aromatic copolymers (C5 / C9 series) petroleum resins, styrene resins, and their hydrides (e.g., alicyclic petroleum resins obtained by hydrogenating aromatic petroleum resins). Other examples of petroleum-based tackifying resins include coumarone / indene resins and dicyclopentadiene resins. Petroleum-based tackifying resins can be used alone or in combination of two or more.

[0076] Examples of styrene-based resins include: resins with styrene homopolymer as the main component, resins with α-methylstyrene homopolymer as the main component, resins with vinyltoluene homopolymer as the main component, and resins with copolymers containing two or more of styrene, α-methylstyrene, and vinyltoluene as the main component (e.g., α-methylstyrene / styrene copolymer resin with α-methylstyrene / styrene copolymer as the main component).

[0077] As a coumarone / indene resin, a resin containing coumarone and indene as monomeric components constituting the resin backbone (main chain) can be used. Examples of monomeric components that can be included in the resin backbone other than coumarone and indene include styrene, α-methylstyrene, methylindene, vinyltoluene, etc.

[0078] Examples of natural tackifying resins include terpene resins and rosin-based resins. Terpene resins include unmodified terpene resins and modified terpene resins. Rosin-based resins include rosin derivative resins. Natural tackifying resins can be used alone or in combination of two or more.

[0079] Examples of terpene resins (unmodified terpene resins) include α-pinene polymers, β-pinene polymers, and dipentene polymers. Examples of modified terpene resins include resins obtained by modifying the above-mentioned terpene resins (phenol modification, aromatic modification (e.g., styrene modification), hydrogenation modification, hydrocarbon modification, etc.). Specifically, examples include terpene phenolic resins, aromatic-modified (e.g., styrene-modified) terpene resins, and hydrogenated terpene resins. Hydrogenated terpene phenolic resins may be included among the above-mentioned terpene phenolic resins.

[0080] The term "terpene phenolic resin" as used above refers to polymers containing terpene residues and phenol residues. It includes both copolymers of terpene and phenolic compounds (terpene-phenol copolymer resins) and resins made by modifying homopolymers or copolymers of terpene (terpene resins, typically unmodified terpene resins) with phenol (phenol-modified terpene resins).

[0081] Specific examples of rosin-based resins include unmodified rosin (raw rosin) such as resin rosin, wood rosin, and tall oil rosin; modified rosin (hydrogenated rosin, disproportionated rosin, polymerized rosin, and rosin with other chemical modifications) obtained by modifying these unmodified rosin through hydrogenation, disproportionation, polymerization, etc.; and so on. Furthermore, examples of rosin derivative resins include: resins obtained by esterifying unmodified rosin with alcohols (i.e., rosin esters); resins obtained by esterifying modified rosin (hydrogenated rosin, disproportionated rosin, polymerized rosin, etc.) with alcohols (i.e., modified rosin esters); unsaturated fatty acid modified rosin obtained by modifying unmodified rosin and modified rosin (hydrogenated rosin, disproportionated rosin, polymerized rosin, etc.) with unsaturated fatty acids; and unsaturated fatty acid modified rosin obtained by modifying rosin esters with unsaturated fatty acids. Saturated fatty acid modified rosin esters; rosin alcohols obtained by reducing the carboxyl groups in unmodified rosin, modified rosin (hydrogenated rosin, disproportionated rosin, polymerized rosin, etc.), unsaturated fatty acid modified rosin, or unsaturated fatty acid modified rosin esters; metal salts of rosin (especially rosin esters), including unmodified rosin, modified rosin, and various rosin derivatives; rosin phenolic resins obtained by adding phenol to rosin (unmodified rosin, modified rosin, various rosin derivatives, etc.) with an acid catalyst and then thermally polymerizing it; etc.

[0082] The tackifying resins used in the techniques disclosed herein typically have a softening point above 40°C, and may be above 60°C. In some embodiments, the softening point of the tackifying resin is above 80°C (e.g., exceeding 80°C), preferably above 100°C (e.g., exceeding 100°C). There is no particular upper limit to the softening point of the tackifying resin; generally, below 200°C is suitable, and from the viewpoint of adhesion, below 180°C is preferred, more preferably below 170°C (e.g., below 160°C), and may be below 140°C or below 120°C.

[0083] Here, the softening point of the tackifying resin in this specification is defined as the value measured based on the softening point test method (ring and ring method) specified in JIS K5902 and JIS K2207. Specifically, the sample is rapidly melted at the lowest possible temperature, and it is filled into a ring placed on a flat metal plate in a manner that avoids the formation of bubbles. After cooling, the raised portion, including the top end of the ring, is cut off from the flat surface using a slightly heated knife. Next, a support (ring stand) is placed in a glass container (heating bath) with a diameter of 85 mm or more and a height of 127 mm or more, and glycerol is poured in until the depth is 90 mm or more. Next, a steel ball (9.5 mm in diameter, 3.5 g in weight) and the ring filled with the sample are immersed in glycerol without contacting each other, and the temperature of the glycerol is maintained at 20 °C ± 5 °C for 15 minutes. Then, the steel ball is placed in the center of the sample surface in the ring and placed in a fixed position on the support. Next, maintaining a distance of 50 mm from the top of the ring to the glycerol surface, place a thermometer with the center of the thermometer's mercury bulb at the same height as the center of the ring, and heat the container. Ensure the Bunsen burner flame used for heating is positioned between the center and edge of the container's bottom to ensure even heating. It should be noted that the bath temperature rise rate after reaching 40°C must be 5.0 ± 0.5°C per minute. The sample gradually softens and flows down the ring, finally contacting the bottom plate; the temperature at this point is recorded as the softening point. Softening point determinations should be performed simultaneously at least twice, and the average value should be used.

[0084] (Hydrogenated hydrocarbon resin)

[0085] In some preferred embodiments, hydrogenated hydrocarbon resins are used as tackifying resins. Here, "hydrogenated hydrocarbon resin" refers to a resin in which at least a portion of a hydrocarbon resin, such as a petroleum resin, has been hydrogenated. The hydrogenated hydrocarbon resin can be partially hydrogenated or fully hydrogenated. Since at least a portion of the hydrogenated hydrocarbon resin is hydrogenated, using it as a tackifying resin can help improve weather resistance. Hydrogenated hydrocarbon resins can be used alone or in combination of two or more.

[0086] The softening point of the hydrogenated hydrocarbon resin is not particularly limited. From the viewpoint of compatibility with adhesives comprising the aforementioned hydrogenated styrene-based block copolymers, the softening point of the hydrogenated hydrocarbon resin is generally preferably 90°C or higher, preferably 95°C or higher, and more preferably 100°C or higher. In some embodiments, the softening point of the hydrogenated hydrocarbon resin may be 105°C or higher, or 110°C or higher. The upper limit of the softening point of the hydrogenated hydrocarbon resin is not particularly limited, but is generally preferably 140°C or lower, preferably 135°C or lower, more preferably 130°C or lower, and even more preferably 125°C or lower. In some embodiments, the softening point of the hydrogenated hydrocarbon resin may be 120°C or lower, 115°C or lower, 110°C or lower, or 105°C or lower.

[0087] The structure of the hydrogenated hydrocarbon resin is not particularly limited. For example, at least a portion of petroleum resins such as aliphatic (C5 series), aromatic (C9 series), and aliphatic / aromatic copolymers (C5 / C9 series) can be hydrogenated hydrocarbon resins. From the viewpoint of compatibility with adhesives comprising the above-mentioned hydrogenated styrene block copolymers, in some embodiments, C5 series or C5 / C9 series hydrogenated hydrocarbon resins are preferred, and C5 series hydrogenated hydrocarbon resins are more preferred.

[0088] In embodiments using hydrogenated hydrocarbon resins, the content of the aforementioned hydrogenated hydrocarbon resins in the adhesive composition (the total amount when containing two or more) is not particularly limited, and an appropriate amount can be used to achieve the desired effect. In some preferred embodiments, the content of the hydrogenated hydrocarbon resin is 50 parts by weight or more, more preferably 75 parts by weight or more, and even more preferably 100 parts by weight or more, relative to 100 parts by weight of the styrene-based block copolymer. In some embodiments, the content of the hydrogenated hydrocarbon resin is 120 parts by weight or more, 130 parts by weight or more, or 140 parts by weight or more, relative to 100 parts by weight of the styrene-based block copolymer. Furthermore, in some preferred embodiments, the content of the hydrogenated hydrocarbon resin is 300 parts by weight or less, more preferably 200 parts by weight or less, and even more preferably 175 parts by weight or less, relative to 100 parts by weight of the styrene-based block copolymer. In some embodiments, the content of the hydrogenated hydrocarbon resin is 150 parts by weight or less, 125 parts by weight or less, or 110 parts by weight or less, relative to 100 parts by weight of the styrene-based block copolymer.

[0089] As hydrogenated hydrocarbon resins, widely known commercially available products can be used. Examples of commercially available products include: ENEOS's "HB-103", "HA-085", "HA-103", "HB-125", "Archon P-100", "Archon P-115", "Archon M-100", and "I-MARV P100".

[0090] (Hydrogenated rosin-based resin)

[0091] In some methods, hydrogenated rosin-based resins are used as tackifying resins. Here, "hydrogenated rosin-based resin" refers to a resin in which at least a portion of the rosin-based resin has been hydrogenated. The hydrogenated rosin-based resin can be partially hydrogenated or fully hydrogenated. Since at least a portion of the hydrogenated rosin-based resin is hydrogenated, using it as a tackifying resin can help improve weather resistance. Hydrogenated rosin-based resins can be used alone or in combination of two or more.

[0092] The aforementioned hydrogenated rosin-based resins are highly compatible with adhesives containing styrene-based block copolymers, and their additive effect can be preferably achieved. While not specifically limited in interpretation, it is believed that the aforementioned hydrogenated rosin-based resins generally possess high-polarity and low-polarity regions within a molecule, and are compatible with the various segments (hard and soft segments) of the aforementioned styrene-based block copolymers, thus contributing to improved adhesive strength. Furthermore, the use of hydrogenated rosin-based resins is also advantageous in improving adhesion to polar substrates such as metals.

[0093] In some preferred embodiments, hydrogenated rosin esters are used as hydrogenated rosin-based resins. The effects of the techniques disclosed herein can be preferably achieved through the addition of hydrogenated rosin esters.

[0094] The softening point of the aforementioned hydrogenated rosin-based resins (e.g., hydrogenated rosin esters) is not particularly limited. From the viewpoint of compatibility with adhesives containing the aforementioned styrene-based block copolymers, the softening point of the hydrogenated rosin-based resin is generally preferably 70°C or higher, preferably 80°C or higher, and more preferably 90°C or higher. The upper limit of the softening point of the hydrogenated rosin-based resin is not particularly limited, but is generally preferably 200°C or lower, preferably 150°C or lower, more preferably 120°C or lower, and even more preferably 110°C or lower.

[0095] In the use of hydrogenated rosin-based resins (e.g., hydrogenated rosin esters), the content of the aforementioned hydrogenated rosin-based resin in the adhesive composition (the total amount if two or more are present) is not particularly limited, and an appropriate amount can be used to achieve the desired effect. In some preferred embodiments, the content of the hydrogenated rosin-based resin is 10 parts by weight or more, more preferably 20 parts by weight or more, and even more preferably 25 parts by weight or more, relative to 100 parts by weight of the styrene-based block copolymer. In some embodiments, the content of the hydrogenated rosin-based resin can be 30 parts by weight or more, 40 parts by weight or more, or 45 parts by weight or more, relative to 100 parts by weight of the styrene-based block copolymer. Furthermore, in some preferred embodiments, the content of the hydrogenated rosin-based resin is 150 parts by weight or less, more preferably 100 parts by weight or less, and even more preferably 60 parts by weight or less (e.g., 50 parts by weight or less), relative to 100 parts by weight of the styrene-based block copolymer.

[0096] As a hydrogenated rosin-based resin, commercially available products are widely used. Examples of commercially available products include "Pine Crystal KE-100" manufactured by Arakawa Chemical Industry Co., Ltd., "Pine Crystal KE-311" manufactured by Arakawa Chemical Industry Co., Ltd., and "Pine Crystal PE-590" manufactured by Arakawa Chemical Industry Co., Ltd.

[0097] In some preferred embodiments, the aforementioned hydrogenated hydrocarbon resin and the aforementioned hydrogenated rosin-based resin (e.g., hydrogenated rosin ester) are used as tackifying resins. By using both hydrogenated hydrocarbon resin and hydrogenated rosin-based resin, the effect of the differences in the chemical structures of each tackifying resin on the styrene-based block copolymer is utilized, easily forming an adhesive with strong adhesion. In embodiments using both hydrogenated hydrocarbon resin and hydrogenated rosin-based resin (e.g., hydrogenated rosin ester), the ratio of their usage is not particularly limited. In some embodiments, the ratio (WT / WS) of the content of hydrogenated hydrocarbon resin (WT) to the content of hydrogenated rosin-based resin (WS) is, for example, 1 or more, preferably 2 or more, and can be 3 or more, 4 or more, 5 or more, or 6 or more. The aforementioned ratio (WT / WS) is, for example, 20 or less, appropriately 16 or less, 12 or less, or 10 or less.

[0098] (Total amount of tackifying resin)

[0099] The total amount of tackifying resin in the adhesive composition is not particularly limited, and an appropriate amount can be used in a manner that achieves the desired effect. In some embodiments, from the viewpoint of improving adhesive strength, the total amount of tackifying resin relative to 100 parts by weight of the styrene-based block copolymer is preferably 75 parts by weight or more, and can be 100 parts by weight or more, or 125 parts by weight or more. Furthermore, in some embodiments, the total amount of tackifying resin relative to 100 parts by weight of the styrene-based block copolymer is 350 parts by weight or less, and can be 300 parts by weight or less, or 250 parts by weight or less. Even with such limitations on the composition of the total amount of tackifying resin, the desired effect can be achieved according to the technology disclosed herein.

[0100] (Softener (E))

[0101] The adhesive compositions disclosed herein preferably contain a softener. The presence of a softener in the adhesive improves adhesion to the adhered materials, thereby enhancing bonding strength. For example, the inclusion of a softener in a high-temperature cohesive composition facilitates the formation of an adhesive that combines strong adhesion with excellent heat resistance. Here, the softener in this specification refers to a liquid or viscous fluid at room temperature (e.g., 25°C), or a material with a softening point below 40°C, typically a liquid hydrocarbon. The softening point can be determined using the same method as that used for determining the softening point of the tackifying resin described above.

[0102] There are no particular limitations on the type of plasticizer; an appropriate plasticizer can be selected based on the composition of the adhesive (type of styrene-based block copolymer, type of tackifying resin, etc.). Examples of plasticizers include: liquid rubbers such as polybutene and polyisoprene; process oils such as alkane-based oils and naphthenic oils; and hydrocarbon synthetic oils such as ethylene-α-olefin co-oligomers. In addition, liquid resins such as liquid terpene resins and liquid rosin-based resins can also be used as plasticizers. Other examples of plasticizers include esters of higher fatty acids such as stearic acid and palmitic acid (higher fatty acid esters) and fatty acid amides. Liquid terpene resins and process oils are preferred. A single plasticizer or a combination of two or more plasticizers can be used.

[0103] The content of the softener in the adhesive composition is not particularly limited, and an appropriate amount can be used in a manner that achieves the desired effect. In some embodiments, the content of the softener, relative to 100 parts by weight of the styrene-based block copolymer, is more than 0 parts by weight and less than 150 parts by weight, and can be 10 to 100 parts by weight. From the viewpoint of improving adhesion, in some preferred embodiments, the content of the softener, relative to 100 parts by weight of the styrene-based block copolymer, is 15 parts by weight or more, more preferably 20 parts by weight or more, and even more preferably 25 parts by weight or more. Furthermore, from the viewpoint of heat resistance, the content of the softener, relative to 100 parts by weight of the styrene-based block copolymer, is preferably 80 parts by weight or less, more preferably 60 parts by weight or less, and even more preferably 50 parts by weight or less.

[0104] (Anti-aging agent)

[0105] The adhesive composition disclosed herein may contain an anti-aging agent as needed. By using an anti-aging agent, the quality stability of the adhesive can be improved. An anti-aging agent may be used alone or in combination of two or more. Examples of anti-aging agents include phosphorus-based antioxidants, phenolic antioxidants (such as hindered phenolic antioxidants), hindered amine antioxidants, aromatic amine antioxidants, and sulfur-based antioxidants. While not particularly limited, the amount of anti-aging agent contained in the adhesive composition disclosed herein, relative to 100 parts by weight of the styrene-based block copolymer, may, for example, be approximately 20 parts by weight or less, typically appropriately 10 parts by weight or less, and may be 5 parts by weight or less. Furthermore, the amount of the aforementioned anti-aging agent, relative to 100 parts by weight of the styrene-based block copolymer, may, for example, be 0.1 parts by weight or more, 0.5 parts by weight or more, or 1 part by weight or more.

[0106] (Other ingredients)

[0107] The adhesive compositions disclosed herein may, as needed, contain various additives commonly found in the field of adhesives, such as leveling agents, crosslinking aids, plasticizers, fillers, colorants (pigments, dyes, etc.), antistatic agents, UV absorbers, and light stabilizers. Such additives can be made using conventionally known substances. Furthermore, the adhesive compositions disclosed herein may contain one or more rubbery polymers other than block copolymers of monovinyl-substituted aromatic compounds and conjugated diene compounds, to a limit that does not impair the effects of the invention. The techniques disclosed herein are preferably implemented in a manner where the aforementioned adhesive compositions substantially do not contain rubbery polymers other than styrene-based block copolymers (e.g., in a manner where the content of the styrene-based block copolymer is 0 to 1 part by weight per 100 parts by weight).

[0108] In some preferred embodiments, the adhesive composition may be composed of a styrene-based block copolymer, a tackifying resin, and a softener, comprising at least 90% by weight of the total weight of the adhesive (i.e., the weight of the adhesive layer constituted by the adhesive). For example, it is preferable to use a composition comprising 90 to 99.8% by weight (typically, for example, 95 to 99.5% by weight) of the total weight of the adhesive.

[0109] The form of the adhesive composition disclosed herein is not particularly limited. For example, it can be a solvent-based adhesive composition in which the adhesive (adhesive component) of the above-described composition is contained in an organic solvent, an aqueous dispersion adhesive composition in which the adhesive is dispersed in an aqueous solvent (water-dispersible type, typically an aqueous emulsion type), or a hot-melt adhesive composition. From the viewpoint of ease of application and freedom of substrate selection, solvent-based or water-dispersible adhesive compositions are preferred. From the viewpoint of achieving higher adhesive performance, solvent-based adhesive compositions are particularly preferred. Furthermore, hot-melt adhesives can be applied in a heated molten state that is substantially free of organic solvents, and are therefore preferred from the viewpoints of productivity and reduced environmental impact.

[0110] Solvent-based adhesive compositions are typically prepared as solutions containing the above-mentioned components in an organic solvent. The organic solvent can be appropriately selected from known or commonly used organic solvents. For example, any one or a mixture of two or more solvents selected from aromatic compounds such as toluene and xylene (typically aromatic hydrocarbons); acetates such as ethyl acetate and butyl acetate; aliphatic or alicyclic hydrocarbons such as hexane, cyclohexane, and methylcyclohexane; haloalkanes such as 1,2-dichloroethane; ketones such as methyl ethyl ketone and acetylacetone; etc. While not particularly limited, the above-mentioned solvent-based adhesive compositions are generally suitably prepared to have a non-volatile component (NV) of 30–65% by weight (e.g., 40–55% by weight).

[0111] Various methods known in the art can be used as methods for obtaining adhesive sheets from adhesive compositions. For example, the following method (direct method) is preferred: an adhesive layer is formed by directly applying (typically coating) the adhesive composition to a substrate and drying it. Alternatively, the following method (transfer method) can be used: an adhesive layer can be formed on a surface with good peelability (e.g., the surface of a release liner, the back of a release-treated support substrate, etc.) by applying the adhesive composition to it and drying it, and then transferring the formed adhesive layer to the substrate.

[0112] The coating of the adhesive composition can be performed using known or conventional coating machines such as gravure roller coaters, reverse roller coaters, slick roller coaters, dip roller coaters, bar coaters, doctor blade coaters, and spray coaters. From the viewpoint of promoting crosslinking reactions and improving manufacturing efficiency, the drying of the adhesive composition is preferably carried out under heat. Typically, a drying temperature of approximately 40°C to 150°C (typically 40°C to 120°C, for example 50°C to 120°C, and further preferably 70°C to 100°C) is preferred. The drying time is not particularly limited and can be set to several tens of seconds to several minutes (for example, approximately 5 minutes, preferably 30 seconds to 2 minutes). Additional drying steps can be added as needed. The adhesive layer is typically formed continuously, but can also be formed into regular or random patterns such as dots or stripes, depending on the purpose and application.

[0113] (Thickness of the adhesive layer)

[0114] While not specifically limited, the thickness of the adhesive layer is preferably about 4 μm or more (e.g., 20 μm or more), and also preferably about 150 μm or less (typically 120 μm or less, e.g., 100 μm or less). In some embodiments, the thickness of the adhesive layer may preferably be 30 μm or more, more preferably 40 μm or more, and even more preferably 50 μm or more (e.g., 60 μm or more). Adhesive sheets with adhesive layers of the above thicknesses can exhibit excellent adhesive performance. In the case of double-sided adhesive sheets with a substrate, a configuration can be formed in which adhesive layers of the above thicknesses are provided on both sides of the substrate. The thickness of each adhesive layer may be the same or different.

[0115] <Example of adhesive sheet structure>

[0116] The adhesive sheet disclosed herein (which can be in the form of a strip or other long strip) can, for example, have... Figure 1The cross-sectional structure of the double-sided adhesive sheet is shown. This double-sided adhesive sheet 1 includes: a substrate (e.g., a plastic film) 15, and a first adhesive layer 11 and a second adhesive layer 12 supported on both sides of the substrate 15, respectively. More specifically, the first adhesive layer 11 and the second adhesive layer 12 are respectively provided on the first side 15A and the second side 15B (both non-peelable) of the substrate 15. The double-sided adhesive sheet 1 before use (before bonding to the substrate) is as follows... Figure 1 As shown, the release liner 21 can be overlapped with and wound into a spiral shape, with both the front surface 21A and the back surface 21B being peelable surfaces. In the double-sided adhesive sheet 1 of the above configuration, the surface of the second adhesive layer 12 (second adhesive surface 12A) is protected by the front surface 21A of the release liner 21, and the surface of the first adhesive layer 11 (first adhesive surface 11A) is protected by the back surface 21B of the release liner 21. Alternatively, the first adhesive surface 11A and the second adhesive surface 12A can be protected by two separate release liners.

[0117] The technology disclosed herein is preferably used for Figure 1 In addition to the double-sided adhesive sheet with substrate shown, it can also be used for Figure 2 The double-sided adhesive sheet 2 shown is a substrate-free (i.e., without a substrate) double-sided adhesive sheet 2 before use, for example as shown below. Figure 2 As shown, the first adhesive surface 11A and the second adhesive surface 11B of the substrate-free adhesive layer 11 can be protected by release liner 21, 22, which are at least the release surfaces of the adhesive layer side surface (front surface). Alternatively, it can be configured as follows: a release liner 21 with both sides serving as release surfaces is used, omitting the release liner 22, and overlapped with the adhesive layer 11 and wound in a spiral shape, thereby the second adhesive surface 11B abuts against the back of the release liner 21 and is protected.

[0118] Furthermore, the technologies disclosed here, such as Figure 3 As shown, it can also be applied to a single-sided adhesive sheet 3 with a substrate, having a substrate 15 and an adhesive layer 11 supported by the first side (non-peel side) 15A of the substrate. The adhesive sheet 3 before use is, for example, as shown... Figure 3 As shown, the adhesive layer 11 can be protected by a release liner 21, which is at least the release surface of the adhesive layer side (front surface). Alternatively, it can be in the following configuration: using a substrate 15 with the second surface 15B as the release surface and omitting the release liner 21, the adhesive sheet 3 with the substrate is wound, thereby the first adhesive surface 11A abuts against and is protected by the second surface 15B of the substrate 15.

[0119] <Substrate>

[0120] When applying the technology disclosed herein to double-sided adhesive sheets or single-sided adhesive sheets with a substrate, the substrate can be, for example, a plastic film such as polypropylene film, ethylene-propylene copolymer film, polyester film, or polyvinyl chloride film, depending on the application of the adhesive sheet; a foamed sheet formed from a foam, such as polyurethane foam, polyethylene foam, or polychloroprene foam; woven fabrics and non-woven fabrics (including paper types such as Japanese paper and premium paper) made from various fibrous materials (such as natural fibers like hemp and cotton, synthetic fibers like polyester and vinylon, and semi-synthetic fibers like acetate) either alone or in blends; metal foils such as aluminum foil and copper foil; etc. As for the aforementioned plastic film (typically referring to non-porous plastic films, a concept distinct from woven fabrics and non-woven fabrics), any film among non-stretchable films and stretched (uniaxially stretched or biaxially stretched) films can be used. Furthermore, surface treatments such as primer coating or corona discharge treatment can be applied to the surface of the substrate where the adhesive layer is located.

[0121] Examples of nonwoven fabrics used as substrates include pulp-based fabrics such as wood pulp; nonwoven fabrics made from natural fibers such as cotton and hemp; nonwoven fabrics made from chemical fibers (synthetic fibers) such as polyester fibers (such as polyethylene terephthalate (PET) fibers), rayon, vinylon, acetate fibers, polyvinyl alcohol (PVA) fibers, polyamide fibers, polyolefin fibers, and polyurethane fibers; and nonwoven fabrics made from two or more different types of fibers. Among these, from the viewpoint of adhesive impregnation and resilience, nonwoven fabrics made from pulp, hemp (e.g., hemp pulp), and PET fibers are preferred. The use of nonwoven fabric substrates also helps improve the softness and tear resistance of the adhesive sheet.

[0122] As a nonwoven fabric (nonwoven fabric substrate), it is preferable to use a material with a unit area mass of approximately 30 g / m². 2 The following (e.g., 25g / m 2 The following is typically 20g / m 2 The following are nonwoven fabrics. The nonwoven fabrics with the above-mentioned unit area mass are suitable for making lightweight adhesive sheets with excellent bonding properties. From the viewpoint of resilience, a unit area mass of less than 18 g / m² is preferred. 2 (e.g., 16g / m) 2 The following is typically 15g / m 2 The following is a nonwoven fabric. From the viewpoint of improving the strength of the substrate itself, the above-mentioned unit area mass is preferably 10 g / m². 2 Above (e.g., 12g / m) 2 The above is typically 13g / m³. 2 above).

[0123] The bulk density of the nonwoven fabric substrate (which can be calculated by dividing the mass per unit area by the thickness) is appropriately about 0.20 g / cm³. 3 The above is preferably 0.25 g / cm³. 3 Above (e.g., 0.30 g / cm³) 3 (above), and appropriately approximately 0.50 g / cm³ 3 The preferred value is 0.40 g / cm³. 3 Below (e.g., 0.35g / cm) 3 (The following). By keeping the bulk density within the above-mentioned range, the substrate itself possesses appropriate strength, resulting in good adhesive impregnation properties. From the viewpoint of resilience, a bulk density of 0.25 to 0.40 g / cm³ is particularly preferred. 3 (e.g., 0.30–0.35 g / cm³) 3 The non-woven fabric substrate is approximately 1000 grams.

[0124] In addition to the aforementioned constituent fibers, the nonwoven fabric substrate may also contain resin components such as starch (e.g., cationic starch), polyacrylamide, viscose, polyvinyl alcohol, urea-formaldehyde resin, melamine-formaldehyde resin, and polyamide-polyamine-epoxychloropropane. These resin components function as paper strength reinforcing agents for the nonwoven fabric substrate. By using these resin components as needed, the strength of the nonwoven fabric substrate can be adjusted. Furthermore, the nonwoven fabric substrate may also contain, as needed, common additives in the field of nonwoven fabric manufacturing, such as yield improvers, filtration agents, viscosity modifiers, and dispersants.

[0125] The thickness of the substrate can be appropriately selected according to the purpose, but it is generally appropriate to set it to approximately 2 μm or more (typically 10 μm or more), and preferably 500 μm or less (typically 200 μm or less). When using nonwoven fabric as the substrate, the thickness of the nonwoven fabric substrate is appropriately about 150 μm or less. From the viewpoint of ensuring that the adhesive is sufficiently impregnated in the entire substrate, the above-mentioned thickness is preferably 100 μm or less (e.g., 70 μm or less). Furthermore, considering the operability during the fabrication of the adhesive sheet, the above-mentioned thickness is preferably 10 μm or more (e.g., 25 μm or more). From the viewpoint of resilience, the above-mentioned thickness is preferably 30 μm or more (e.g., 35 μm or more, typically 40 μm or more), and preferably 60 μm or less (e.g., 50 μm or less, typically 45 μm or less).

[0126] <Thickness of the adhesive sheet>

[0127] The total thickness of the adhesive sheet disclosed herein (including the thickness of the adhesive layer and the substrate, but excluding the thickness of the release liner) is not particularly limited. From the viewpoints of thinning, lightweighting, and resource conservation, it is preferably set to about 1000 μm or less (e.g., 500 μm or less, typically 300 μm or less), and can be 150 μm or less. Furthermore, from the viewpoints of ensuring good adhesive properties, it is appropriately set to 50 μm or more (e.g., 70 μm or more, typically 100 μm or more).

[0128] <Removing the Lining>

[0129] As the release liner, conventional release paper or the like can be used, without particular limitation. For example, release liners with a release treatment layer on the surface of a substrate such as plastic film or paper, or release liners formed from low-adhesion materials such as fluoropolymers (polytetrafluoroethylene, etc.) or polyolefin resins (polyethylene, polypropylene, etc.) can be used. The aforementioned release treatment layer can, for example, be formed by surface treatment of the substrate with release agents such as silicone-based, long-chain alkyl-based, fluorine-based, or molybdenum sulfide.

[0130] <Characteristics of Adhesive Sheets>

[0131] The adhesive sheet disclosed herein exhibits an adhesion strength (SUS adhesion strength) of at least 15 N / 20 mm, measured under conditions of 23°C, 50% RH, tensile speed of 100 mm / min, and peel angle of 180 degrees, to stainless steel (SUS304BA). This indicates that the adhesive sheet with the aforementioned SUS adhesion strength can provide sufficient adhesion to the adhered objects. From the viewpoint of adhesion, the aforementioned SUS adhesion strength is more preferably at least 25 N / 20 mm, further preferably at least 28 N / 20 mm, and particularly preferably at least 30 N / 20 mm. It should be noted that the upper limit of the aforementioned SUS adhesion strength is not particularly limited; for example, it can be approximately 50 N / 20 mm or less. A 2 kg roller is used to press the surface of the stainless steel (SUS304BA) adhered object once back and forth. After 30 minutes, the SUS adhesion strength is measured according to JIS Z 0237 under conditions of tensile speed of 100 mm / min and peel angle of 180 degrees. The SUS adhesion strength was determined more specifically by the method described in the examples described later.

[0132] The adhesive sheet disclosed herein exhibits an adhesion strength (PP adhesion strength) of at least 10 N / 20 mm, measured under conditions of 23°C, 50% RH, tensile speed of 100 mm / min, and peel angle of 180 degrees. This adhesive sheet demonstrates sufficient adhesion to difficult-to-bond materials. From the viewpoint of adhesion to difficult-to-bond materials, the aforementioned PP adhesion strength is more preferably at least 13 N / 20 mm, further preferably at least 19 N / 20 mm (e.g., at least 20 N / 20 mm), and particularly preferably at least 23 N / 20 mm. It should be noted that the upper limit of the aforementioned PP adhesion strength is not particularly limited; for example, it can be approximately 45 N / 20 mm or less. The PP surface, which is the substrate, is pressed against a 2 kg roller once, and after 30 minutes, the PP adhesion strength is measured according to JIS Z 0237 under conditions of tensile speed of 100 mm / min and peel angle of 180 degrees. The PP adhesive strength was measured more specifically by the method described in the examples described later.

[0133] The adhesive sheet disclosed herein, when tested for holding force against a stainless steel sheet under conditions of 90°C, an adhesive area of ​​10mm × 30mm, a load of 500g, and a holding time of 1 hour, preferably does not fall off. The adhesive sheet satisfying the above characteristics exhibits excellent high-temperature holding force and is not prone to peeling or shifting even when used in a manner exposed to high temperatures, easily achieving excellent bonding reliability. Specifically, the above holding force test is performed by the method described in the examples described later.

[0134] <Uses>

[0135] The adhesive compositions or adhesive sheets disclosed herein are useful for joining components in various OA equipment (e.g., PCs), household appliances (e.g., rice cookers, refrigerators), automobiles, building materials (e.g., residential building materials), etc. (e.g., for fixing various parts in the aforementioned articles).

[0136] Example

[0137] The following description describes some embodiments of the present invention, but it does not imply that the present invention is limited to the contents shown in the embodiments. It should be noted that, in the following description, "parts" and "%" are based on weight unless otherwise specified. Furthermore, unless otherwise specified, the amounts of each material are based on amounts excluding solvents.

[0138] <Example 1>

[0139] (Preparation of the adhesive composition)

[0140] The following materials were prepared: 100 parts of maleic anhydride-modified styrene / ethylene / butene / styrene block copolymer (manufactured by Kraton Polymers, product name "FG1924", styrene content 13%, maleic acid modification 1%) as acid-modified hydrogenated styrene block copolymer (A); 150 parts of hydrogenated hydrocarbon resin (manufactured by Arakawa Chemical Industry Co., Ltd., product name "Archon P-100", softening point 100℃) as tackifying resin (D); 50 parts of hydrogenated rosin ester (D2) (manufactured by Arakawa Chemical Industry Co., Ltd., product name "PineCrystal PE-590", softening point 90-100℃); 25 parts of liquid hydrocarbon (ethylene-α-olefin coolidomer, manufactured by Mitsui Chemicals Co., Ltd., product name "Lucant LX400") as softening agent (E); and polyphenylene ether (manufactured by SABIC, product name "Noryl") as polyphenylene ether resin (C). 10 parts of SA-120 (softening point 165℃), 0.3 parts of aluminum triacetylacetonate (manufactured by Matsumoto Fine Chemical Co., Ltd., product name "AL-3100") as crosslinking agent (B), and toluene as solvent were stirred and mixed to prepare an NV50% adhesive composition.

[0141] (Making the adhesive sheet)

[0142] The adhesive composition described above was applied to the release-treated surface of a 75 μm thick PET film treated with a silicone-based release agent, and dried at 120°C for 3 minutes to form an adhesive layer with a thickness of 70 μm. A release liner treated with a silicone-based release agent was then bonded to the surface of the adhesive layer. The sheet was stored at 40°C for at least 24 hours. This produced the adhesive sheet of this example (a substrate-free double-sided adhesive sheet with a release liner).

[0143] <Examples 2-8 and Comparative Examples 1-5>

[0144] The types and amounts of tackifying resin, softeners, polyphenylene ether resin, and crosslinking agents were varied as shown in Tables 1-2. Otherwise, the adhesive compositions of each example were prepared in the same manner as in Example 1, and the adhesive sheets of each example were made using each adhesive composition in the same manner as in Example 1.

[0145] It should be noted that the materials used are shown in the table below.

[0146] (Acid-modified hydrogenated styrene block copolymer)

[0147] "FG1924": A product name manufactured by Kraton Polymers, containing 13% styrene and 1% maleic anhydride modified SEBS.

[0148] (Tackifying resin)

[0149] "P-100": The product name "Archon P-100" manufactured by Arakawa Chemical Industry Co., Ltd., is a hydrogenated hydrocarbon resin with a softening point of 100°C.

[0150] “P-115”: The product name “Archon P-115” manufactured by Arakawa Chemical Industry Co., Ltd., is a hydrogenated hydrocarbon resin with a softening point of 115°C.

[0151] "PE-590": The product name "Pine Crystal PE-590" manufactured by Arakawa Chemical Industry Co., Ltd. is a hydrogenated rosin ester with a softening point of 90-100℃.

[0152] (Softener)

[0153] "LX400": An ethylene α-olefin coolidomer manufactured by Mitsui Chemicals under the product name "Lucant LX400".

[0154] "HV-1900": Polybutene manufactured by ENEOS under the product name "Polybutene HV-1900".

[0155] (Polyphenylene ether resin)

[0156] "SA-120": Polyphenylene oxide manufactured by SABIC under the product name "Noryl SA-120".

[0157] (Cross-linking agent)

[0158] “AL-3100”: Aluminum triacetylacetonate with the product name “AL-3100” manufactured by Matsumoto Fine Chemical Co., Ltd.

[0159] <Evaluation Methods>

[0160] (180° peel strength)

[0161] Peel off the release liner from one adhesive side of the cover adhesive sheet (double-sided adhesive sheet), laminate it onto a 75 μm thick polyethylene terephthalate (PET) film, and mount it. Cut the mounted adhesive sheet into pieces 20 mm wide and 100 mm long to create test pieces. At 23°C and 50% RH, expose the other adhesive side (the test surface) of the test piece, and press the exposed adhesive side of the test piece against the surface of the substrate using a 2 kg roller in a reciprocating motion. After placing it in this environment for 30 minutes, measure the 180° peel adhesion force [N / 20 mm] using a tensile testing machine at a tensile speed of 100 mm / min according to JIS Z 0237. Stainless steel sheet (SUS304BA) and PP sheet (manufactured by Hitachi Chemical Co., Ltd.) were used as the substrates, and the adhesion force was measured separately according to the above steps. The obtained values ​​are recorded in the "To SUS" and "To PP" columns of Tables 1 and 2.

[0162] It should be noted that when using single-sided adhesive sheets as test pieces for testing, the mounting of the PET film is not necessary.

[0163] (Holding force)

[0164] Peel off the release liner from one adhesive side of the cover adhesive sheet (double-sided adhesive sheet), laminate it onto a 50μm thick PET film, and mount it. Cut the mounted adhesive sheet into strips 10mm wide to create test pieces. In an environment of 23°C and 50% RH, expose the other adhesive side (the test object side) of the test piece, and press it against a 2kg roller once, with an adhesive area of ​​10mm width and 30mm length, onto a stainless steel plate (SUS304) used as the substrate. After placing the test piece against the substrate in this environment for 30 minutes, hang the substrate vertically along the length of the test piece, apply a 500g load to the free end of the test piece, and, according to JIS Z 0237, place it at 60°C, 70°C, 80°C, or 90°C for 1 hour under this load. If it does not fall after 1 hour, it is considered to have sufficient high-temperature holding power at the test temperature. For each adhesive sheet, three test pieces were used for the test (i.e., n=3). During the 1-hour period, even if one test piece fell, it was evaluated as "fall". In Tables 1 and 2, the highest temperature among the test temperatures that did not fall after 1 hour was recorded in the "Holding Temperature" column, and the lowest temperature among the test temperatures that fell was recorded in the "Fall Temperature" column.

[0165] It should be noted that when using single-sided adhesive sheets as test pieces for testing, the mounting of the PET film is not necessary.

[0166] The summaries and evaluation results of each case are shown in Tables 1-2.

[0167] [Table 1]

[0168]

[0169] [Table 2]

[0170]

[0171] As shown in Tables 1-2, the adhesive sheets of Examples 1-8, which contain acid-modified hydrogenated styrene block copolymer, tackifying resin, polyphenylene ether resin, and crosslinking agent, were found to have significantly superior high-temperature retention and improved heat resistance compared to the adhesive sheets of Comparative Examples 1-3, which do not contain crosslinking agent. Furthermore, the adhesive sheets of Examples 1-8, which contain acid-modified hydrogenated styrene block copolymer, tackifying resin, polyphenylene ether resin, and crosslinking agent, were also found to exhibit superior high-temperature retention and improved heat resistance compared to the adhesive sheets of Comparative Examples 1, 4, and 5, which do not contain polyphenylene ether resin.

[0172] Furthermore, the adhesive sheets of Examples 1-6, with a polyphenylene ether resin to crosslinking agent content ratio within a specific range, exhibit particularly high adhesive strength compared to the adhesive sheets of Examples 7 and 8.

[0173] The specific examples of the present invention have been described in detail above, but these are merely examples and do not limit the scope of the claims. The technology described in the claims includes technologies derived from the specific examples above through various modifications and alterations.

[0174] Explanation of reference numerals in the attached figures

[0175] 1, 2, 3: Adhesive sheets; 11: First adhesive layer; 12: Second adhesive layer; 15: Substrate; 21, 22: Release lining.

Claims

1. An adhesive composition comprising: Acid-modified hydrogenated styrene block copolymer A, A cross-linking agent B that can react with acid, Polyphenylene ether resin C, and Tackifying resin D.

2. The adhesive composition according to claim 1, wherein The ratio of the content WB of the crosslinking agent B capable of reacting with an acid to the content WC of the polyphenylene ether resin C, namely WB / WC, is 3 / 97 or more and 7 / 93 or less, The units of the content WB and the content WC are weight %.

3. The adhesive composition according to claim 1 or 2, wherein The acid-modified hydrogenated styrene-based block copolymer A is a maleic anhydride-modified hydrogenated styrene-based block copolymer.

4. The adhesive composition according to any one of claims 1 to 3, wherein The acid-modified hydrogenated styrene-based block copolymer A is a maleic anhydride-modified styrene-ethylene-butylene-styrene block copolymer.

5. The adhesive composition according to any one of claims 1 to 4, wherein The cross-linking agent B capable of reacting with acid is a metal compound.

6. The adhesive composition according to any one of claims 1 to 5, wherein The cross-linking agent B capable of reacting with acid is metal acetylacetonate.

7. The adhesive composition according to any one of claims 1 to 6, wherein The crosslinking agent B capable of reacting with acid is tris(acetylacetonate)aluminum.

8. The adhesive composition according to any one of claims 1 to 7, wherein The polyphenylene ether-based resin C is polyphenylene ether.

9. The adhesive composition according to any one of claims 1 to 8, wherein The tackifying resin D comprises a hydrogenated hydrocarbon resin and a hydrogenated rosin ester.

10. The adhesive composition according to any one of claims 1 to 9, wherein Also contains softener E.

11. The adhesive composition according to any one of claims 1 to 10, wherein The content of the acid-reactive crosslinking agent B is 0.3 parts by weight or more and 1.3 parts by weight or less relative to 100 parts by weight of the acid-modified hydrogenated styrene-based block copolymer A.

12. The adhesive composition according to any one of claims 1 to 11, wherein The content of the polyphenylene ether-based resin C is 10 parts by weight or more and 20 parts by weight or less relative to 100 parts by weight of the acid-modified hydrogenated styrene-based block copolymer A.

13. The adhesive composition according to claim 9, wherein The content of the hydrogenated hydrocarbon resin is 100 parts by weight or more and 150 parts by weight or less relative to 100 parts by weight of the acid-modified hydrogenated styrene-based block copolymer A.

14. The adhesive composition according to claim 9, wherein The content of the hydrogenated rosin ester is 30 parts by weight or more and 50 parts by weight or less relative to 100 parts by weight of the acid-modified hydrogenated styrene-based block copolymer A.

15. The adhesive composition according to claim 10, wherein The softener E is contained in an amount of 25 parts by weight or more and 50 parts by weight or less relative to 100 parts by weight of the acid-modified hydrogenated styrene-based block copolymer A. 16 . A pressure-sensitive adhesive sheet comprising a pressure-sensitive adhesive layer formed from the pressure-sensitive adhesive composition according to claim 1 .

Citation Information

Patent Citations

  • JP1975057626A

  • Adhesive polymer composition

    JP2000212345A

  • Eating bird carcass alignment device

    JP2022087533A